Powdery Mildews in the Libyan Jamahiriya: III. Identity of Certain Powdery Mildew Fungi - KHAN, M. WAJID; FARAJ, I. S. (The Libyan Journal of Agriculture, 2023)
This paper, third in the series, presents the identity of certain powdery mildew fungi infecting cultivated and wild plants in the Libyan Jamahiriya. It includes Erysiphe pisi, E. communis, E. cichoracearum, Sphaerothecafuliginea and Leveillula taurica on certain hosts not described in this series. The occurrence of these powdery mildew species on most of the hosts are new records for the Jamahiriya. Some are also new to the host index of the species.